Climate warming and bumble bee declines: the need to consider sub-lethal heat, carry-over effects, and colony compensation - White, Sabrina A.; Dillon, Michael E. (Frontiers in Physiology, 2023)
Global declines in abundance and diversity of insects are now well-documented and increasingly concerning given the critical and diverse roles insects play in all ecosystems. Habitat loss, invasive species, and anthropogenic chemicals are all clearly detrimental to insect populations, but mounting evidence implicates climate change as a key driver of insect declines globally. Warming temperatures combined with increased variability may expose organisms to extreme heat that exceeds tolerance, potentially driving local extirpations. In this context, heat tolerance limits (e.g., critical thermal maximum, CTmax) have been measured for many invertebrates and are often closely linked to climate regions where animals are found. However, temperatures well below CTmax may also have pronounced effects on insects, but have been relatively less studied. Additionally, many insects with out-sized ecological and economic footprints are colonial (e.g. ants, social bees, termites) such that effects of heat on individuals may propagate through or be compensated by the colony. For colonial organisms, measuring direct effects on individuals may therefore reveal little about population-level impacts of changing climates. Here, we use bumble bees (genus Bombus) as a case study to highlight how a limited understanding of heat effects below CTmax and of colonial impacts and responses both likely hinder our ability to explain past and predict future climate change impacts. Insights from bumble bees suggest that, for diverse invertebrates, predicting climate change impacts will require a more nuanced understanding of the effects of heat exposure and additional studies of carry-over effects and compensatory responses by colonies.